Game and Decision Theory Applied to Business, Economy and Finance (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
Game theory is the branch of Mathematics dedicated to the design of models that are able to make predictions, under the assumption that the agents under interaction (negotiation) are rational. Game theory can be applied to several different research fields, including computer and social sciences. It has been applied in business, financial decisions, presidential elections, jury decisions in trials, and biology in general. The origin of game theory is from the necessity of taking logical decisions inside conflicts and negotiations when several possible choices emerge. Within game theory, the information available for each player is crucial for making decisions. Besides game theory, Quantum Mechanics, oriented to finance, dubbed Quantum Finance, is a new branch of science where decision theories can be explored in a more logical way. This Special Issue is a combination of game theory and Quantum Finance, with the purpose of solving multiple problems related to individual and collective rational decisions.